Population genetic structure of black rats in an urban environment: a case study in Cotonou, Benin - Badou, Sylvestre; Gauthier, Philippe; HOUEMENOU, GUALBERT; Loiseau, Anne; DOSSOU, Henri_Joël; Etougbétché, Jonas; HOUÉMÉNOU, Honoré; AGBANGLA, CLÉMENT; Brouat, Carine; Dobigny, Gauthier (My University, 2021)
The cosmopolitan black rat, Rattus rattus, has invaded many cities throughout the world. Although the species is responsible for major damages to food stocks and crops and is involved in the maintenance, circulation and transmission of many zoonotic pathogens to humans and animals, a lot remains to be known about its eco-evolutionary characteristics, especially in highly modified environments like the urban habitat. In particular, very few studies were conducted on the genetic structure of urban black rat populations, which is yet a prerequisite for defining effective management units. Here, we focus on the population genetics of Rattus rattus in Cotonou, Benin. Forty different localities were sampled throughout the city and 457 individuals were genotyped using 18 microsatellite markers. Our results reveal two poorly distinguishable but significant genetic clusters, one of each side of Cotonou channel, that tend to homogenize into a single group due to probable gene flow between the two shores. Implications in terms of management units and rodent control are discussed.
Keywords: population genetics; urban ecology; biological invasion; Africa; rodent control